Kesiapan UMKM Handicraft Surabaya Menghadapi Masyarakat Ekonomi ASEAN (MEA) Melalui Peningkatan Kualitas dan Kuantitas Produk Ekspor - Kresnawati, Megahnanda Alidyan; Andarini, Sonja; Anabarja, Sarah (Global and Policy Journal of International Relations, 2016)
ABSTRACTThe establishment of ASEAN Economic Community (AEC) has become one of the challenge for Small and Medium Enterprises (SMEs) in Indonesia. The challenges are especially in the way of how to increase the standard, design and product quality so that they can survive in the ASEAN single market. As one of the proven safety net in Indonesian economy after the crisis in 1998, SMEs became in the point of attention in Indonesian economic development. Thus, in order to develop the Indonesian economic performance, SMEs are needed to increase their number of exports as well as their management. According to the 2004 report, in Surabaya there are only 30 percent of SMEs products which are successfully market their products abroad. These numbers are still lesser than the expected percentage of export number from SMEs. By using the qualitative method this research identifies the obstacles and challenges faced by the SMEs producing Handicrafts products in Surabaya. As for the data were obtained by interview and FGD technic. The result of this first phase is going to be used to form the education pattern for developing the performance for those SMEs by using the Problem Based Learning Model.Keywords : Small and Medium Enterprises (SMEs), Handicraft, Export Products, QualityDOI : https//doi.org/10.33005/jgp.v4i02.1910